Job Involvement as an Outcome of Organizational Justice - Shrestha, Prakash (NCC Journal, 2019)
This research paper aims to examine employee perceptions of job involvements an outcome of organizational justice in Nepalese context. It is based upon the perceptions of 765 employees of 18 commercial banks and 6 insurance companies of Nepal. This study uses a six Point Likert-type scale for measurement of the perception of job involvement and organizational justice. Based on empirical results, this study shows that organizational justice is positively associated with job involvement. All three justice dimensions such as distributive, procedural and interactional justices play key roles in making employees more involved in their job in Nepalese organizations. If employees perceive any kind of justice in the organization in terms of rewards, outcomes, rules, communication, and interactions, they will fully involve in their jobs and organizational activities.